Revisit Intention Framework: Is It Real that Cultural Contact and Destination Attractiveness Can Have Direct Impact? - Yunfin, Meidarina; Kusumah, Echo Perdana; MS, Mahrinasari; Reniati, Reniati (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2023)
This study uses survey responses from 321 Indonesian tourists to examine the connection between cultural contact, destination attractiveness, visitor satisfaction, and the likelihood of a revisit intention to Himpang Lime Habang in the South Bangka regency of the Bangka Belitung province, Indonesia. Two significant findings from this investigation were obtained using Partial Least Squares-Structural Equation Modeling methods. The first finding is the correlation between satisfaction and the likelihood of future visits. Furthermore, a visitor's desire to return is unaffected by the attractiveness of a destination or the amount of cultural contact they have. Even though exposure to local culture and a destination's natural beauty can considerably enhance a visitor's experience, they have little bearing on whether or not someone will return.